1956
DOI: 10.1149/1.2430329
|View full text |Cite
|
Sign up to set email alerts
|

Closure to “Discussion of ‘High Temperature Oxidation of Two Zirconium-Tin Alloys’ [M. W. Mallett and W. M. Albrecht (pp. 407–414)]”

Abstract: The oxygen consumed is used up in two processes: (a) solution in the metal, and (b) forination of an oxide fihn. Have the authors any estimate, either experimental or from diffusion calculations, of the amount used in each process? ~I. W. MALLETT AND W. M. ALBRECHT: Calculations based upon diffusion data indicate that about 0.5 1.5% of the total amount of oxygen consumed by a reacted specimen was used up in the diffusion process. Normal variations in rate data are greater than this. In the proposed mechanism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
1

Year Published

1956
1956
1974
1974

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 0 publications
3
26
1
Order By: Relevance
“…If intrinsic ionization (Eq. [4]) predominates, the electrical conductivity is independent of oxygen pressure and the concentration of electrons (or electron holes) is given by [e-] = K41/2 [5] 2. If intrinsic ionization is negligible, the electrical conductivity is determined by Eq.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…If intrinsic ionization (Eq. [4]) predominates, the electrical conductivity is independent of oxygen pressure and the concentration of electrons (or electron holes) is given by [e-] = K41/2 [5] 2. If intrinsic ionization is negligible, the electrical conductivity is determined by Eq.…”
Section: Resultsmentioning
confidence: 99%
“…For HfO2 it is proposed that when the conductivity due to the coupled transport becomes too small, the conductivity due to intrinsic ionization will predominate and the conductivity will become essentially independent of oxygen pressure (Eq. [5]). This behavior is observed for HfOe at Poe < 10-B-10-s atm.…”
Section: Portional To Poementioning
confidence: 99%
See 2 more Smart Citations
“…Large temperature gradients existed along the condenser, and it was concluded that the heating was not uniform. Resistance heating was substituted in the last four tests (l6 through 19) in an attempt to provide uniform temperature control. Uniform heating of the condenser was observed up to the time of distillation.…”
Section: B Magnesium Distillation Studiesmentioning
confidence: 99%